PENENTUAN NILAI PANGKAT PADA ALGORITMA FUZZY C-MEANS - WULAN ANGGRAENI (LPPM, 2015)
The purpose of this study was to determine the value of rank of the fuzzy c-means algorithm that generates cluster with a good accuracy. The selection value of the square of the yield rate of 92% with central point is . the selection of the value of the cube produce an accuracy rate of 85% with central point is . While election rank value of 4 produce an accuracy rate of 62% with central point is . Every selection the rank was value produce first cluster for the student with tendency IPS and the second group for the student with tendency IPA. It can be concluded that the rank value of 2 yields the highest accuracy. Keyword: clustering, fuzzy, fuzzy c-means